Optimal Design of Nonuniform Linear Arrays in Cellular Systems by Out-of-Cell Interference Minimization - S. Savazzi (EURASIP Journal on Wireless Communications and Networking, 2007)
Optimal design of a linear antenna array with nonuniform interelement spacings is investigated for the uplink of a cellular system. The optimization criterion considered is based on the minimization of the average interference power at the output of a conventional beamformer (matched filter) and it is compared to the maximization of the ergodic capacity (throughput). Out-of-cell interference is modelled as spatially correlated Gaussian noise. The more analytically tractable problem of minimizing the interference power is considered first, and a closed-form expression for this criterion is derived as a function of the antenna spacings. This analysis allows to get insight into the structure of the optimal array for different propagation conditions and cellular layouts. The optimal array deployments obtained according to this criterion are then shown, via numerical optimization, to maximize the ergodic capacity for the scenarios considered here. More importantly, it is verified that substantial performance gain with respect to conventionally designed linear antenna arrays (i.e., uniform ÃŽÂ»/2 interelement spacing) can be harnessed by a nonuniform optimized linear array.